2022
DOI: 10.3389/fmars.2022.878301
|View full text |Cite
|
Sign up to set email alerts
|

Model Simulation of Storm Surge in the Northwestern South China Sea Under the Impact of Sea Level Rise: A Case Study of Super Typhoon Rammasun (2014)

Abstract: Because of global warming, the sea level is expected to continue to rise, possibly having a significant impact on the intensities and spatial distribution characteristics of coastal storm surges. In this study, we took super typhoon Rammasun (2014) as a case study and applied the SCHISM (Semi-implicit Cross-scale Hydroscience Integrated System Model) to simulate storm surge in the northwestern South China Sea under future sea level rise (SLR) scenarios. To improve the accuracy of storm surge hindcast, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, a warm current coming from Beibu Gulf via Qiongzhou Strait flowed along the northern coast of the Island. Zhou et al (2022) found that the east-west water level gradients at the Strait are responsible for this warm current.…”
Section: Response Of Hydrodynamic Processesmentioning
confidence: 98%
“…In addition, a warm current coming from Beibu Gulf via Qiongzhou Strait flowed along the northern coast of the Island. Zhou et al (2022) found that the east-west water level gradients at the Strait are responsible for this warm current.…”
Section: Response Of Hydrodynamic Processesmentioning
confidence: 98%
“…In order to achieve an accurate simulation of storm surges, various factors need to be considered, such as the configuration of shoreline and bathymetry, the value of bottom friction coefficient, and most importantly, the precision of typhoon wind field (Zhou et al, 2022). For the numerical simulation and prediction of storm surges, there are many kinds of wind fields that can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Landfalling TCs accompanied by strong winds, which can trigger storm surges and rainfall that can further aggravate heavy rainfall disasters, represent a disaster-causing factor that cannot be ignored [3]. Super Typhoon Rammasun (2014), which was the strongest typhoon ever recorded to make landfall in China [4,5], had characteristics of multiple landings, rapid intensification, and maintained intensity. The maximum wind speed near the TC center reached 72 m/s when it first made landfall in Wenchang, Hainan Province [6].…”
Section: Introductionmentioning
confidence: 99%